Modelling of Sturm-Liouville’s Problem via Deformable Derivative - Anju Dhiraj Kumar Naidu, Anisa Ahmad, Ajay Dixit, Amit Ujlayan (Journal of Daoist Studies, 2026)
This paper presents new results based on a recently proposed deformable derivative [12]. We formulate the Sturm–Liouville problem using the deformable derivative and derive several significant results, including the Rayleigh quotient, criteria for functional dependence and independence via the Wronskian in the deformable derivative framework, and the characterization of the eigenvalues of the deformable-derivative Sturm–Liouville problem.